Pengaruh Home Care Terhadap Tingkat Kemandirian Keluarga Dalam Merawat Penyakit Diabetes Mellitus Tipe 2 - Alkhusari A; Serli Wulan Safitri; Reka Dellis Alfiyanti (Penerbit Yayasan Daarul Huda Kruengmane, 2022)
Type 2 Diabetes Mellitus is a chronic hyperglycemic condition that triggers various chronic complications. Families that have a good level of independence in caring for diabetic members can prevent complications from occurring. Family independence can be increased through home care services. The purpose of this study was to determine the effect of Home Care services on the level of Family Independence in Caring for Family Members with Type 2 Diabetes Mellitus at the Puskesmas Plaju in 2022. This type of research was a quasi-experimental study using a nonrandomized control group pretest-posttest design . Data collection was carried out at August 8-28, 2022 on 30 samples. The research test used the Wilcoxon Sign Rank Test and the Mann Whitney U Test . The results of the Mann Whitney U Test obtained a p-value of 0.000 so that the p-value < 0.05, meaning that there is an effect of home care services on the level of family independence in caring for family members with type 2 Diabetes Mellitus. The conclusion of this study is that there is an effect of home care services. on the level of family independence.